2019
DOI: 10.1371/journal.pone.0213749
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring breast cancer response to neoadjuvant chemotherapy with ultrasound signal statistics and integrated backscatter

Abstract: BackgroundNeoadjuvant chemotherapy (NAC) is used in patients with breast cancer to reduce tumor focus, metastatic risk, and patient mortality. Monitoring NAC effects is necessary to capture resistant patients and stop or change treatment. The existing methods for evaluating NAC results have some limitations. The aim of this study was to assess the tumor response at an early stage, after the first doses of the NAC, based on the variability of the backscattered ultrasound energy, and backscatter statistics. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The results showed that tumor stiffness and BS at t2 had the best performance, which is consistent with the optimal time point reported in previous studies with MRI and PET (34,35). This finding may be attributed to the following reason: NACT initially alters the biomechanical properties and microvascular perfusion in the tumor, whereas morphological changes that can be observed on imaging occur later (33,36). Several studies also showed that tumor size variation is not a sensitive index to distinguish responders from non-responders (37).…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that tumor stiffness and BS at t2 had the best performance, which is consistent with the optimal time point reported in previous studies with MRI and PET (34,35). This finding may be attributed to the following reason: NACT initially alters the biomechanical properties and microvascular perfusion in the tumor, whereas morphological changes that can be observed on imaging occur later (33,36). Several studies also showed that tumor size variation is not a sensitive index to distinguish responders from non-responders (37).…”
Section: Discussionsupporting
confidence: 89%
“…30 The ultrasonic signal statistics and integrated backscatter can monitor the response to NAC effectively. 31 Ultrasound can measure the axillary lymph node response to NAC accurately also 32 .However, ultrasound is operator-dependent, and breast cancer typically becomes less cellular after NAC, even if no marked decrease in size is observed. 33 Sometimes ultrasound imaging of residual tumor burden is insufficient to predict the actual response to neoadjuvant chemotherapy with adequate accuracy.…”
Section: Ultrasound Evaluationmentioning
confidence: 99%
“…The IBC was determined from the backscattering coefficient in the frequency range 5–12 MHz, corresponding to the transducer band. The method was described in detail previously 13 . A reference phantom (1126 B, Dansk Phantom Service) was used in the measurements and the RF data was collected from a 3 × 3 mm window, which was a sufficient size to provide reliable values of scattering parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Another promising direction for the early evaluation of tumour responses to NAC therapy is the use of quantitative ultrasound (QUS). Some initial studies were able to identify changes on QUS as early as one week after NAC, using parameters such as integrated backscattering coefficient (IBC) and average acoustic concentration 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%